When Civil Society Defends Authoritarianism: Thai Bhakdi, We Support Prayuth, and Thailand’s Democratic Decline - Sapta, Igastya Hagarayu; Makhasin, Luthfi (Jurnal Politik, 2025)
Civil society is often regarded as an essential foundation for democratic consolidation, but in Thailand, civil society also plays a crucial role in maintaining authoritarian rule. This article analyzes how pro-authoritarian civil society movements—Thai Bhakdi and “We Support Prayuth”—emerged and operated in the context of the historical relationship between the military and the monarchy and political polarisation since the 2006 coup. Using the authoritarian civil society (ACS) framework and a comparative historical analysis approach, this study traces how the long-standing divide between reformist and conservative forces created fertile ground for these movements. Thai Bhakdi, rooted in monarchist nationalism, mobilises offline and digital activism to defend the monarchy, emphasising national identity and using lèse majesté laws to silence criticism. “We Support Prayuth,” in line with the military-led narrative of stability, legitimises extraordinary powers such as Article 44 to strengthen the junta’s authority. Using archival data, academic literature, and social media content, the findings show that these movements—though formally independent from the state—function as autonomous enforcers of the royal-military-conservative order. Rather than countering authoritarianism, Thailand’s polarised civil society has legitimised it, narrowing the space for democracy and reinforcing a path-dependent cycle of democratic backsliding.